Survival Study of D-dimer, Lactic Acid and BGA on COVID-19 Patients - Purwadi Sujalmo; Rosita Yunanda Purwanto; Clarista Ardelia Rahardjo; Yanasta Yudo Pratama; Rochmi Isnaini Rismawanti; Wandira Lalitya; Afridhia Bidari Fachrudin (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
The value of D-dimer value, lactic acid levels, and the results of blood gas analysis (PaO2, PCO2, PH, and PaO2/FiO2) are prognostic factors for COVID-19 patients, although there is no agreement on the optimum cut-off point for specificity and sensitivity. The aim of this study is to examine D-dimer value, lactic acid levels, and the results of blood gas analysis as a prognosis for patients with severe or critical COVID-19. This was a retrospective study of the medical records of the UGM Academic Hospital. Overall survival was assessed by the Kaplan-Meier curve. Determination of the cut-off for D-dimer, lactic acid, and BGA variables was carried out using the ROC followed by calculating the Youden index. Then the hazard ratio was determined by Cox regression. The cut-off value to determine the group of patients on the D-dimer and lactic acid variable was 881 ng/mL (sensitivity 77.23%, specificity 32.31%) (p=0.040) and 21 ng/mL, patients with lactic acid values above the cut-off had a higher risk of death (p=0.391). The cut-off of pH, PaO2, and PaCO2 were 7.43, 72.2 mmHg, and 33.9, respectively. D-dimer levels, lactic acid, and PaCO2 values in blood gas analysis above the cut-off value had a worse survival rate, while patients also had a worse survival rate if the PaO2 and PH values were below the cut-off value.